The Correlation Between Safety Climate With Unsafe Act In Apartment Building Construction Workers Pt. Multikon 2020 - Rahmah Amalina; Rahmah Hida Nurrizka; Fandita Tonyka Maharani (Journal of Public Health Research and Community Health Development, 2021)
Construction is one of the highest industries in contributing to work accident rates. Unsafe act is the cause of 73% of work accidents. One way to prevent unsafe act is through safe behavior implemented by management and workers themselves. This study aims to determine the correlation between the safety climate with unsafe act. This research uses quantitative analytic methods with cross sectional design study. Data was analyzed using chi-square with a sample of 88 people selected by purposive sampling method. The results showed that the proportion of respondents who frequently perform unsafe acts was 33%. In bivariate analysis showed there were a relevant relationship between the dimensions of management safety empowerment (OR 2.455; 95% CI 1.06-5.87), worker’s safety priority and risk non-acceptance (OR 2.679; 95% CI 1.05- 6,83) and the dimensions of safety communication, learning and trust in co-worker’s safety competence (OR 2,500; 95% CI 1.05-5.91) with unsafe act. Workers who have a good perception of a safety climate rarely take unsafe actions.